2015
DOI: 10.1371/journal.pone.0130817
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Load Carriage and Physical Fatigue on Cognitive Performance

Abstract: In the current study, ten participants walked for two hours while carrying no load or a 40 kg load. During the second hour, treadmill grade was manipulated between a constant downhill or changing between flat, uphill, and downhill grades. Throughout the prolonged walk, participants performed two cognitive tasks, an auditory go no/go task and a visual target detection task. The main findings were that the number of false alarms increased over time in the loaded condition relative to the unloaded condition on th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
47
3

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 40 publications
(53 citation statements)
references
References 19 publications
3
47
3
Order By: Relevance
“…muscle activity, motion artifact) 5,24,50 . Behavioral studies of walking with a heavily loaded rucksack have demonstrated changes in biomechanics of gait including ground reaction force, step length, body segment acceleration, and muscle activation 12,28,51,52 , all of which have been identified as sources of noise in EEG. Our results show that we were able to measure the expected waveforms and topography related to a visual discrimination task during walking with a heavily loaded rucksack.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…muscle activity, motion artifact) 5,24,50 . Behavioral studies of walking with a heavily loaded rucksack have demonstrated changes in biomechanics of gait including ground reaction force, step length, body segment acceleration, and muscle activation 12,28,51,52 , all of which have been identified as sources of noise in EEG. Our results show that we were able to measure the expected waveforms and topography related to a visual discrimination task during walking with a heavily loaded rucksack.…”
Section: Discussionmentioning
confidence: 99%
“…The rating of perceived exertion was significantly different across the three conditions: seated, unloaded walking, and loaded walking. We did not include measures of biomechanics or energetics in our study, but there is ample evidence from past studies that the addition of 40% body weight load during walking substantially affects gait biomechanics and metabolic measures 12,28,51,52 . Although we did not measure it, we also observed increased amounts of sweating with the greater rucksack load.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The large decrease in vertical jump measures in the second day of this study are thought to be due to the timetabling of the selection course. Candidates were tasked with both a load carriage event and another task with a high number of stairs on the first night, which would have elicited high levels of neuromuscular fatigue [ 28 ] leading to decreases in both physical and cognitive performance [ 29 , 30 ]. Additionally, a greater amount of rest was given after the first night, which may also have had some contribution to the relative improvements in performance in the latter stages of the week.…”
Section: Discussionmentioning
confidence: 99%